If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 = -4(-6a + -2) + -1(8 + 6a) Reorder the terms: 54 = -4(-2 + -6a) + -1(8 + 6a) 54 = (-2 * -4 + -6a * -4) + -1(8 + 6a) 54 = (8 + 24a) + -1(8 + 6a) 54 = 8 + 24a + (8 * -1 + 6a * -1) 54 = 8 + 24a + (-8 + -6a) Reorder the terms: 54 = 8 + -8 + 24a + -6a Combine like terms: 8 + -8 = 0 54 = 0 + 24a + -6a 54 = 24a + -6a Combine like terms: 24a + -6a = 18a 54 = 18a Solving 54 = 18a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-18a' to each side of the equation. 54 + -18a = 18a + -18a Combine like terms: 18a + -18a = 0 54 + -18a = 0 Add '-54' to each side of the equation. 54 + -54 + -18a = 0 + -54 Combine like terms: 54 + -54 = 0 0 + -18a = 0 + -54 -18a = 0 + -54 Combine like terms: 0 + -54 = -54 -18a = -54 Divide each side by '-18'. a = 3 Simplifying a = 3
| x^3-3x+2=1 | | -5x=-3y-0 | | z+(10z-126)+(10z-42)=189 | | w^2+8=4 | | 2.5x-2(2.3+3x)=-4.6-3.5 | | 4x+12-4x=32+2x | | 11+n=35 | | x+4=-1+2x | | 4s-9=0 | | 22n=44 | | -54=6(2+7a)-2(5a+7) | | 71=-5(7n-1)-2(3n+8) | | 7-6m=l | | 8(n+6)-3(5n-5)=63 | | -4s+st+2t-8= | | 12p=-13 | | 3.9(10+9)= | | 5(6x+2)-6(4x+7)=-20 | | .38x=175 | | 2t-8+st-4s= | | 78=4(8p-4)+5(5p-4) | | x-5cosx=0 | | x^2+x-34=-3x-2 | | (12+7x)=9x | | 132=-6-6(3-3k) | | 110=5(1-3n) | | 81=-x-7(x-7) | | 6(5+4x)=-162 | | 19x=9x | | -6(1+5n)=-156 | | 7[9-(3x-4)]=105x+203 | | 7a-3+8=12 |